Review and analysis of experiences in the field of sustainable development with land use planning approach - Mojtaba, Mofareh Bonab.; Ali, Majnoony Tootakhane.; Khadijeh, Ebrahimi (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
Sustainable use of the soil is a form of land management which retains the natural fertility of the soil and allows the production of food and fibre supplies and renewable natural resources on a long-term basis. It implies that the natural environment should be treated and managed in such a way that the cycles and energy flows among the soil, bodies of water and atmosphere are preserved or restored. To this respect, the term “sustainable land use” is more comprehensive than the term “sustainable soil use”. The term "land" commonly, stands for a section of the earth’s surface with all the physical, chemical and biological features that influence the use of the resource. It refers to soil, spatial variability of landscape, climate, hydrology, vegetation and fauna, and also includes improvements in land management, such as drainage schemes, terraces and other agrobiological and mechanical measures. The term “land use” encompasses not only land use for agricultural and forestry purposes, but also for settlements, industrial sites, roads and other human activities. Land use, in this meaning, can be termed sustainable only if it achieves such a spatial distribution or configuration of the different uses as to guarantee biodiversity and preserve the ecobalance of the whole system. Rational land use planning is fundamental to this process. With reference to these issues, this paper describes the main physical, social and economic features of land use planning projects, along with their environmental impacts and the constraints to sustainable development. The importance and role of institutional strengthening, sound financial and managerial frameworks, and the availability of human resources are analyzed, along with research thrust, technology transfer and networking improvement.